Analisis Strategi Pemasaran Produk Pembiayaan Multi Guna (PMG) dalam Meningkatkan Jumlah Nasabah pada Bank Sumut Syariah Capem Panyabungan - Siti Kholijah; Muhammad Ramadhan Pratama Lubis; Riski Adi; Dedi Syafriansyah; Yaumun Nur Rahayu Lubis; Siti Annisa; Masroani Siregar; Mutiah; Nikmah Hayati; Zelvi Selvia Rima Safitri; Lukman Nur Hakim (PT. Willy Print Art, 2026)
This community service aims to analyze and optimize the marketing strategy of the Multi-Purpose Financing (PMG) product to increase the number of customers at Bank Sumut Syariah Capem Panyabungan. The main problem identified is the low level of public understanding of Islamic financing products and limited promotional activities, which affect customer growth. The method used is a qualitative approach with a participatory assistance model through observation, problem identification, counseling, and discussions with bank staff. The results show that implementing marketing strategies through the marketing mix (product, price, place, and promotion) and community socialization activities can increase public understanding and interest in PMG products. In conclusion, well-planned marketing strategies based on public education can increase the number of customers and strengthen public trust in Islamic banking services.